Periodic business and exchange rate cycles: Evidence from 7 emerging markets - Karsten Köhler; Engelbert Stockhammer (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2020)
The paper investigates exchange rate cycles and their relationship to the business cycle in 7 major emerging market economies. We document the presence of periodic cycles in nominal US-dollar exchange rates and show that these are closely aligned with cycle frequencies in real output. Joint fluctuations in exchange rates and output exhibit frequencies between 4 and 8 years. We consider external and internal driving forces of those periodic cycles. There is moderate evidence of co-movements in exchange rates across countries that are strongly linked to global commodity prices, but only weakly so to US monetary policy or global uncertainty shocks. However, estimated periodicities in external factors do not match the periodicities found in exchange rates, thus leaving an important cycle property unexplained. We therefore test for the presence of a cyclical interaction mechanism between exchange rates and output that may transform external shocks into periodic oscillations. We find evidence for such an interaction mechanism, consistent with the recent literature on the financial channel of exchange rates, for Chile and South Africa, and partly for the Philippines.
Keywords: E12; E32; F31; C32; 330; Business cycles; exchange rate cycles; emerging market economies; global financial cycle; commodity prices; monetary policy spillovers; financial channel of exchange rates